What special precautions are required while anesthetizing COVID-19 patients in the operation room? - Nasrin Aghazade; Allahveirdy Arjmand; Mohammad Arabsorkhi; Vahid Rahmani (Journal of Preventive Epidemiology)
On The emergence of the COVID-19 pandemic has impacted not only the daily routines of individuals, but also the procedural approaches of medical and anesthesia experts, encompassing surgical procedures, operating room administration, patient welfare, and healthcare personnel. One of the most susceptible direct contact groups with COVID-19 patients is the operating room staff. The primary objective of this investigation is to conduct a literature review of specific articles pertaining to the requisite precautions during anesthesia administration for patients afflicted with COVID-19. The literature was carried out in PubMed, Web of Science, and Scopus were used to search for English-language articles. All type of articles was included. Keywords were COVID-19, novel coronavirus, 2019- nCoV, coronavirus disease 2019, operating room, theatre, measures, medical staff, health providers, and anesthesia. In this study, we aimed to identify essential information needed by operating room staff, especially anesthesiologists, to manage the entire anesthesia process in COVID-19 patients in a relatively safe manner. We found that necessary points included avoiding the airway and other biologic secretions such as cerebrospinal fluid and blood, using fiber-optic or video laryngoscopy, adequate pre-oxygenation with a well-fitted mask, avoiding awake intubation, selecting a rapid sequence approach, using disposable equipment, delaying elective surgery, and wearing a N95 mask, eye shield, gown, and gloves.